2009
DOI: 10.1016/j.juro.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Trial to Compare Shock Wave Frequencies of 60 and 120 Shocks per Minute for Upper Ureteral Stones

Abstract: Decreasing the rate of shock wave administration from 120 to 60 shocks per minute results in improved stone-free rates. A slower treatment rate of proximal ureteral stones reduces the need for additional shock wave lithotripsy or more invasive treatments to render patients stone-free, without any increase in morbidity, and with an acceptable increase in treatment time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…One study showed that the mean number of SWL sessions required was reduced in patients undergoing fast SWL (p = 0.021) [51]. The other study showed that duration of procedure was significantly reduced in patients undergoing fast SWL compared to slow SWL (p < 0.001) [53]. A similar result was reported in one study [56] but no p-value was reported.…”
Section: Swl Prone Versus Swl Supinementioning
confidence: 65%
See 2 more Smart Citations
“…One study showed that the mean number of SWL sessions required was reduced in patients undergoing fast SWL (p = 0.021) [51]. The other study showed that duration of procedure was significantly reduced in patients undergoing fast SWL compared to slow SWL (p < 0.001) [53]. A similar result was reported in one study [56] but no p-value was reported.…”
Section: Swl Prone Versus Swl Supinementioning
confidence: 65%
“…In one study, there was no significant difference in the achieved SFR at 2 wk [50], whereas in the other study, these rates were improved by treating the patient prone rather than supine (90.6% vs 88.3%, p < 0.05) [49]. Three studies looked at whether the administered shock rate affected SFRs [51,53,56]. In all studies, SFRs were higher when shock waves were administered at a slower rate, reaching a statistically significant difference (p < 0.05) in one study [53].…”
Section: Swl Prone Versus Swl Supinementioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41][42][43] This may also reduce the degree of renal injury, which may be an issue for upper ureteric stones, but is likely less relevant for mid and distal ureteral stones. Slowing treatment rate does increase treatment times.…”
Section: Treatment Ratementioning
confidence: 99%
“…In 1984, the first commercially available lithotripter (HM3) was introduced. 3 The technology was derived as a spinoff from military research. The aerospace firm Dornier noted unusual patterns of metal fatigue in aircrafts and theorized that shock waves created by raindrops striking an aircraft in supersonic flight could cause metal fatigue.…”
Section: Extracorporeal Shock Wave Lithotripsymentioning
confidence: 99%